Classification of Program Types and Cost Prediction of Integrated Care for the Elderly - Moon, Byunggeor (Frontiers in Public Health, 2022)
Abstract This paper analyzes the types of community-based integrated care programs based on the needs of consumers and estimates future costs through data on consumer-oriented integrated care for the elderly in the local community operated by Korea, which is experiencing rapid aging. By analyzing the types of programs and the composition of budget items, we check the composition of the program from the consumer side of the integrated care program in the local community and predict the national budget for each item to operate it. Through this, policy implications for business operation and implications for sustainable financial management are derived. • Ethics approval and consent to participate: Not applicable • Consent for publication: Not applicable • Availability of data and material: Not applicable • Competing interests: The authors declare that they have no competing interests • Funding: Not applicable • Authors' contributions: Corresponding authors • Acknowledgements: Not applicable